2016
DOI: 10.1200/jco.2016.34.4_suppl.196
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib/II study of BBI608 combined with weekly paclitaxel in advanced pancreatic cancer.

Abstract: 196 Background: Cancer stemness is thought to be associated with resistance to chemotherapies. BBI608, a first-in-class cancer stemness inhibitor that works through inhibiting the Stat3 pathway, has shown potent synergistic anti-tumor activity with paclitaxel in vivo. In a phase Ib dose escalation study in patients with advanced solid tumors, BBI608 plus weekly paclitaxel was well tolerated and a RP2D of BBI608 480 mg BID was determined. Methods: Patients with heavily pretreated metastatic pancreatic adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In combination with chemotherapeutic drugs, full-dose napabucasin (500 mg, twice daily) and paclitaxel has passed safety and tolerability tests and shown encouraging clinical responses in patients with different advanced solid tumors, including gastric and gastroesophageal junction (GEJ) adenocarcinoma [91], platinum-resistant ovarian cancer (PROC) [92], pancreatic ductal adenocarcinoma (PDAC) [93], triple-negative breast cancer (TNBC) [94] and other cancer types [90] in individual cohorts of a phase Ib/II trial (NCT01325441). Particularly, in the gastric and GEJ adenocarcinoma cohort, this combination has shown promising results in both taxane-naïve ( n = 16) and taxane-exposed patients ( n = 19), with DCR being 75% versus 68% [91].…”
Section: Clinical Trials Of Stat3 Targeting Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with chemotherapeutic drugs, full-dose napabucasin (500 mg, twice daily) and paclitaxel has passed safety and tolerability tests and shown encouraging clinical responses in patients with different advanced solid tumors, including gastric and gastroesophageal junction (GEJ) adenocarcinoma [91], platinum-resistant ovarian cancer (PROC) [92], pancreatic ductal adenocarcinoma (PDAC) [93], triple-negative breast cancer (TNBC) [94] and other cancer types [90] in individual cohorts of a phase Ib/II trial (NCT01325441). Particularly, in the gastric and GEJ adenocarcinoma cohort, this combination has shown promising results in both taxane-naïve ( n = 16) and taxane-exposed patients ( n = 19), with DCR being 75% versus 68% [91].…”
Section: Clinical Trials Of Stat3 Targeting Therapiesmentioning
confidence: 99%
“…So far, napabucasin is the only STAT3-targeted drug that has been clinically studied in combination with other therapies. As discussed before, early-phase trials have revealed promising antitumor efficacy when combining napabucasin with standard chemodrugs including paclitaxel [90,91,92,93,94], gemcitabine plus nab-paclitaxel [99] and FOLFIRI with or without bevacizumab [97,98], as well as another targeted drug panitumumab [95,96] in several solid malignancies. Preclinical results have also suggested that napabucasin may synergize with paclitaxel to overcome drug resistance [86] and sensitize CRC to immune checkpoint inhibitors in syngeneic tumor models [124].…”
Section: Clinical Trials Of Stat3 Targeting Therapiesmentioning
confidence: 99%
“…A second pancreatic study enrolling 41 patients, all of whom had received two prior lines of chemotherapy (including 5-fluorouracil, leucovorin, irinotecan and oxaliplatin combination chemotherapy and gemcitabine/nab-paclitaxel), combined napabucasin with weekly paclitaxel. Here, of 31 evaluable patients, the disease control rate was 48% [43]. In colorectal cancer, a phase Ib study of napabucasin in combination with 5-fluorouracil, leucovorin and irinotecan combination chemotherapy (FOLFIRI) with and without bevacizumab showed that in 18 heavily pretreated patients (10 of whom had previously progressed on FOLFIRI), disease control was observed in 94% of the 16 evaluable patients [44].…”
Section: Phase I Ib/ii and Iii Clinical Trials Of Napabucasin (Bbi608)mentioning
confidence: 95%
“…Napabucasin (BBI608) is a small molecule inhibitor of STAT3 evaluated for the treatment of several cancers including platinum-resistant ovarian cancer, gastric adenocarcinoma, and pancreatic cancer [99]. A phase Ib/II study tested napabucasin in combination with nab-paclitaxel for pre-treated metastatic PDAC [100]. Results were promising with a response rate of 7%, and a disease control rate of 52% in evaluable patients (n = 31).…”
Section: Stat3 Inhibitionmentioning
confidence: 99%